F(x)dx = G(x) and (F-1(x)dx = AF-1(...
Question
Fullscreen

F(x)dx = G(x) and (F-1(x)dx = AF-1(x) – G(B)+c, then Alx is equal to

JEE/Engineering Exams
Maths
Solution
144
Rating
4.0 (1 ratings)
Fullscreen
LHS ( f f^{-1}(x) d x=A F^{-1}(x)-G(B)+C ) [ begin{array}{l}x=F(t) d x=F^{prime}(t) d t int t F^{prime}(t) d t =t F(t)-int F(t) d t =t F(t)-G(t) =F^{-1}(x) x-Gleft(f^{-1}(x)right) A=x text { ce } A / x=1^{prime}=F^{prime prime}end{array} ]
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free